부챗말 추출액이 H₂O₂에 의한 혈관내피세포주인 ECV304세포의 산화적 스트레스에 미치는 영향 - 박진모(Jin Mo Park); 주성민(Sung Min Ju); 전병제(Byung Jae Jeon); 양현모(Hyun Mo Yang); 최한길(Han kil Choi); 전병훈(Byung Hoon Jeon); 김원신(Won Sin Kim) (동의생리병리학회지, 2008)
The marine algae, Padina arborescens, have been used traditionally for treatment of various brain diseases. However, the molecular studies on the effect of Padina arborescens have not been carried out. In the present study, the protective effect of the water extract of Padina arborescens (PAWE) was researched in H2O2-treated human vascular endothelial cells, ECV304. ECV304 cells were pre-incubated with PAWE (0, 400, 800, 1,200 and 1,600 ㎍/㎖) for 12 h and treated with 500 uM H2O2 for 12 h, and then the protective effects of PAWE were determined. PAWE recovered the H2O2-induced cell damage and decreased ROS production in ECV304 cells. Moreover, PAWE increased ERK expression and inhibited p38 and JNK expression. Furthermore, PAWE dose- dependently increased the expression of heme oxygenase-1 (HO-1) and the HO-1 expression was reduced by ERK inhibitor treatment in H2O2-treated EVC304 cells. These results suggested that protective effect of PAWE on H2O2-induced oxidative stress in ECV304 cells might be associated with the production of HO-1 through the ERK signal pathway. The marine algae, Padina arborescens, have been used traditionally for treatment of various brain diseases. However, the molecular studies on the effect of Padina arborescens have not been carried out. In the present study, the protective effect of the water extract of Padina arborescens (PAWE) was researched in H2O2-treated human vascular endothelial cells, ECV304. ECV304 cells were pre-incubated with PAWE (0, 400, 800, 1,200 and 1,600 ㎍/㎖) for 12 h and treated with 500 uM H2O2 for 12 h, and then the protective effects of PAWE were determined. PAWE recovered the H2O2-induced cell damage and decreased ROS production in ECV304 cells. Moreover, PAWE increased ERK expression and inhibited p38 and JNK expression. Furthermore, PAWE dose- dependently increased the expression of heme oxygenase-1 (HO-1) and the HO-1 expression was reduced by ERK inhibitor treatment in H2O2-treated EVC304 cells. These results suggested that protective effect of PAWE on H2O2-induced oxidative stress in ECV304 cells might be associated with the production of HO-1 through the ERK signal pathway. KCI Citation Count: 0